Use of polypropylene mesh in superior posterior thoracoplasty - S. A. Belov; A. A. Grigoryuk (Вестник хирургии имени И.И. Грекова)
The objective was to evaluate the possibilities of using the polypropylene mesh “Surgipro” to increase the compression and reduce the operational injury in extrapleural superior posterior thoracoplasty.Material and methods. 64 cases of surgical treatment of fibrous-cavernous tuberculosis were studied. The volume of compression of the lung tissue and the effectiveness of the intervention were compared.Results. Clinical and radiologic examination of patients in three weeks after the operation indicates that occurrence of exacerbation, preservation of bacterial excretion and lack of compression are much lower in the group using polypropylene mesh. The use of polypropylene mesh “Surgipro” increases the degree of compression in the field of intervention and the effectiveness of thoracoplasty.Conclusion. The use of a mesh implant in thoracoplasty is reasonable and effective.